Efektivitas Media Roda Kebangsaan: Penerapannya Dalam Meningkatkan Konsentrasi Belajar Siswa SDI An-Nur Tumpang - Rahmawati, Fadilla Agnesia; Fadilla, Aura Sinta Noor; Adi Dharma, Muhammad Naufal Wahyu; Annazhifa, Nafla; Nurohmah, Yesika Hanun; Eka Putra, Surya Desismansyah (Universitas Muhammadiyah Ponorogo, 2026)
Problems that arise in the classroom learning process suggest that some students may not be paying sufficient attention to teaching and learning activities. This condition has an impact on the low effectiveness of learning and makes students tend to be more passive, such as not daring to express their opinions, having difficulty in making decisions, and showing high dependence on others. This study aims to measure the level of learning interest of students at SDI AN-NUR using a quantitative approach. The research subjects consisted of 25 fifth-grade students. The learning media used were the national wheel as a means to increase student involvement and participation. This study used a quantitative method in the form of a pretest and posttest of students, as well as using the national wheel indicator in the form of a satisfaction questionnaire from educators and students in the application of learning media. Data analysis was carried out technically through score calculations, pretest and posttest grouping, and learning media suitability. The results showed that the average score using the national wheel media was 72.2 (pretest) and 87.36 (posttest) after using the national wheel method. The gain score between the pretest and posttest scores was 15.16. It is hoped that the implementation of national education media will help students become more active in the learning process, increase their courage in expressing their opinions, and support the development of independent thinking skills more optimally.